2019
DOI: 10.1370/afm.2448
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Burnout and Practice Organization in Family Physicians

Abstract: PURPOSE Burnout has been reported to be as high as 63% among family physicians and has negative effects on physicians, patients, and the medical system. There are likely structural causes of burnout, but little is known about the relationship between practice organization and burnout. Our objective was to study this association in family physicians. METHODS This cross-sectional study uses secondary data supplied by practicing physicians from the 2017 American Board of Family Medicine (ABFM) Family Medicine Cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 34 publications
1
32
0
6
Order By: Relevance
“…Additionally, one-third of rural physicians in our survey (33.3%) reported being a faculty member. Consistent with previous findings, 20 our data suggest that FPs tend to be primarily employed in hospital-owned practices (40.9% of rural FPs and 32.9% of urban FPs) followed by group private practice (20.8% of rural FPs and 23.7% of urban FPs). In our study, we found no significant difference in burnout between rural (45.1%) and urban (43.0%) FPs.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, one-third of rural physicians in our survey (33.3%) reported being a faculty member. Consistent with previous findings, 20 our data suggest that FPs tend to be primarily employed in hospital-owned practices (40.9% of rural FPs and 32.9% of urban FPs) followed by group private practice (20.8% of rural FPs and 23.7% of urban FPs). In our study, we found no significant difference in burnout between rural (45.1%) and urban (43.0%) FPs.…”
Section: Resultssupporting
confidence: 92%
“…We found small differences in burnout by practice organization and percent vulnerable population, but no difference by scope of practice or rural location. Consistent with past work, 20,21 FPs in practice environments with lack of control over workload, less time for documentation, and more chaos and stress were more likely to report burnout.…”
Section: Resultsmentioning
confidence: 52%
“…We assessed burnout using two items that correspond to the emotional exhaustion and depersonalization scales of the Maslach Burnout Inventory. 24 Following past work, [25][26][27] we defined burnout as responses to either the emotional exhaustion or depersonalization items at "once a week or more" or more frequently. We characterized whether the resident was meeting expectations on the professionalism milestones at each evaluation starting with a 4 at the end of year PGY-3 rating and removing 0.5 points for each of the preceding ratings.…”
Section: Methodsmentioning
confidence: 99%
“…But here again, there is little research to support a causal relationship with burnout. 8 In the absence of clear and convincing proof, we are left to imagine why burnout is such a burning issue. We are left with our own experiences; we are left with what we choose to believe.…”
Section: From the Editormentioning
confidence: 99%